Bosonic Dp-branes at finite temperature in TFD approach - Abdalla, M. C.B. [UNESP]; Gadelha, A. L. [UNESP]; Vancea, I. V. (Elsevier, 2004)
A general formulation of Thermo Field Dynamics using transformation generators that form the SU(1,1) group, is presented and applied to the closed bosonic string and for bosonic Dp-brane with an external field. © 2004 Published by Elsevier B.V.